HYDRAULICS OF HORIZONTAL WELLS IN FRACTURED SHALLOW AQUIFER SYSTEMS - Park E.; Zhan H. (My University, 2003)
An analysis of groundwater hydraulic head in the vicinity of a horizontal well in fractured or porous aquifers considering confined, leaky confined, and water-table aquifer boundary conditions is presented. Solutions for hydraulic heads in both leaky confined and water table aquifers are provided. The fracture model used in this study is the standard double-porosity model. The aquitard storage is included in the formula. Solutions for the confined and unconfined conditions, fractured and porous conditions, wellbore storage, and skin effect are compared. Several findings of this study are, (1) the influence of wellbore storage and skin upon the drawdown for a fractured confined aquifer is similar to that for a porous confined aquifer, (2) aquitard storage affects the intermediate time the most by delaying the drawdown, and (3) there is a significant difference between the type curves of fractured and porous confined aquifers in most aquifer boundary conditions because of the contribution of matrix storage, and such a difference disappears at the later time.
Keywords: HORIZONTAL WELL; WELLBORE STORAGE; SKIN EFFECT; WATER TABLE; LEAKY CONFINED AQUIFER; FRACTURED AQUIFER